ACTH in Infantile Spasms - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The relationship between dose of ACTH and the initial effect and long-term prognosis was investigated in 41 children with infantile spasms at the Department of Pediatrics, Kyoto University, Kyoto, Japan.